Neonatal complications of newborns children born of immigrant mothers in comparison with local mothers: A view of a growing immigration to Ecuador (Research, Society and Development, 2021)
Background: In the last years, there has been a great migratory flow to Ecuador. Purpose: To determine if there are differences in the morbidity of children born of immigrant mothers or local mothers. Methods: epidemiological, observational, cross-sectional study, with two cohorts of patients, newborns from immigrant mothers, and local mothers. 220 individuals were analyzed. Results: 90.45% of the mothers were between 18 and 35 years old; 49.09% had a free-union marital status, 32.27% were single, 18.18% married, and 0.45 divorced, homemakers in the 75.91%, with temporarily leased housing, 89.09% live with close relatives. In 54.55%, the income was between 61 to 400 USD, 66.36% eat three meals in a day, and 70.46% of mothers had five or more prenatal controls. In 71.90% of cases, it performed prenatal controls in the facilities of the Ministry of Health in Ecuador, and it made 18.10% in their country of origin, Colombia, or Venezuela. The most common maternal risk factor was UTIs in 60.57% of mothers, followed by preeclampsia and syphilis. Conclusion: Children born from immigrant mothers have a higher number of neonatal complications. Most immigrant mothers arrive in conditions of poverty and get occasional and temporary jobs that allow them to earn an income of between 30 to 400 USD per month. This low income has a direct effect on the nutritional status of the mother and the fetus. Additionally, these mothers have a lower number of prenatal controls, of low quality, and more connate infections. The circle of immigrant poverty has direct health complications.